Respect and civilizing processes. Socio-psychic overlap of emotions (Praxis Educativa, 2016)
In this paper we present a set of approaches on the phenomenon of respect in its socio-psychic dimension, in order to achieve a deeper understanding of the emotional structure that adolescents construct in the school life dimension. Our fundamental premise is that in our capitalist societies respect is a scarce symbolic asset. Consideration for others is the result of a complex and arduous civilizing process. The fear of losing reputation or social esteem and personal degradation stands as a regulator of behavior and as an effective mechanism of control and self-control of emotions. Social arragements determine and stipulate specific modes of linking through mutual respect as part of an emotional and historical sociocultural configuration matrix.
Keywords: respect; emotional structure; adolescents students; figurational sociology